The Kiel policy package to address the crisis in the euro area - Dennis J. Snower; Jens Boysen-Hogrefe; Klaus-Jürgen Gern; Henning Klodt; Stefan Kooths; Claus-Friedrich Laaser; Christopher Reicher; Björn van Roye; Joachim Scheide; Klaus Schrader (Kiel Institute for the World Economy (IfW), 2013)
The European Union at the crossroads - Thirteen years after its foundation, the European Monetary Union (EMU) is facing the greatest challenge of its history thus far. High unemployment in a number of member countries, the need for substantial consolidation of the budgets of numerous governments, and distressed banks are symptoms of economic misalignments and economic policy failure that threaten not only economic prosperity in Europe, but the European project as a whole. A series of interrelated fiscal and financial crises in the euro area have provoked a series of extraordinary policy measures. Some of these measures have undermined the fiscal sovereignty of affected countries, and they have circumvented market mechanisms. As social cohesion is called into question in various debtor countries, there is a danger that policy makers cannot or will not solve the existing problems in a way consistent with both monetary stability and the current political integration. In the absence of a comprehensive European financial policy regime, the Eurosystem's ability to maintain both price stability and financial stability is threatening to become undermined (see Box 1). Possible outcomes include the chaotic dissolution of the EMU, with unpredictable economic and social consequences. The purpose of this Policy Brief is to outline a set of mechanisms to ensure economic, financial, social and political stability.
Keywords: 330